Planning and urban violence suffered by women in Barrio Nuevo (La Plata) - María Sofía Bernat (Cuaderno Urbano, 2021)
This paper aims to analyze the urban planning of Barrio Nuevo (La Plata) and then to investigate the role of such planning in the daily urban violence suffered by the women who live there. Barrio Nuevo is a neighborhood that emerged after the 2013 flood from the relocation of settlements that were next to El Gato stream. The questions we start with are the following: How has the urban planning of Barrio Nuevo been? Does access to brick houses guarantee access to the right to the city? What kind of violence do women mention? How does planning affect the daily violence they suffer in the public space? The methodology is qualitative-ethnographic. Participant observations and in-depth interviews were conducted between 2013-2019.